A rate-based approach to cleaning-in-place - Trinh, Linda; Willey, A. Roy; Martin, Peter J.; Ashley, Jon; Tothill, Ibtisam E.; Rodgers, Thomas Lawrence (American Chemical Society, 2017)
Fouling is a major problem in the food industry. In cases where allergens are involved, excessive cleaning of food processing equipment often takes place to ensure allergen levels are reduced to acceptable levels. Experimental trials were conducted in a pilot scale cleaning rig to assess the effect of fluid flow rate and temperature on the removal rate of milk paste during cleaning-in-place. Conductivity measurements taken during trials were analysed to produce an equation enabling calculation of the cleaning rate with water temperature, flow rate, initial deposit mass, and time. The rate of cleaning with detergent was also investigated. This methodology produces a rate based expression for cleaning which can be applied to other products, and can be used to determine the time when cleaning is complete, the extent of a cleaning process, or when the pre-rinse should be replaced with a detergent rinse. This prevents over-cleaning and therefore reduces the costs associated with over-cleaning through energy, material and loss of production time.
Keywords: Transport Phenomena and Fluid Mechanics; Cleaning-In-Place (CIP); Cleaning Rate; Fouling